2019
DOI: 10.1021/acs.jpcc.9b03924
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of X-ray Damage to Perfluorosulfonic Acid Using Correlative Microscopy

Abstract: Polymer electrolytes such as perfluorosulfonic acid (PFSA) are key to a variety of electrochemical and clean energy applications. Many analytical techniques for characterizing nanostructured devices containing polymer electrolytes use high-energy electrons or X-rays, which can severely damage soft matter. To better analyze these materials, it is important to understand the chemical, physical, and spectroscopic changes that occur due to radiation damage. Soft X-ray damage to PFSA was characterized using a combi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 60 publications
(141 reference statements)
2
13
0
Order By: Relevance
“…Similar to the case described in Section 3.4, we deduced the corresponding values using the tabulated photoabsorption cross sections (Henke et al, 1993) for the elements contained in Nafion 117, and then we obtained the photoabsorption cross section Calc: Nafion at 685 eV (705 eV) as 2916 cm 2 g À1 (11320 cm 2 g À1 ) accordingly. By referring the measured optical density of perfluorosulfonic acid (PFSA) at the F 1s peak at 690 eV (Martens et al, 2019), we could estimate the photoabsorption cross section Exp: Nafion at 690 eV to be about 23540 cm 2 g À1 . By using these photoabsorption cross sections and the density of Nafion 117, we calculated the transmission T(E x ) for each excitation energy as shown in Table 1.…”
Section: X-ray Absorbed Dose For the Typical Xrf Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar to the case described in Section 3.4, we deduced the corresponding values using the tabulated photoabsorption cross sections (Henke et al, 1993) for the elements contained in Nafion 117, and then we obtained the photoabsorption cross section Calc: Nafion at 685 eV (705 eV) as 2916 cm 2 g À1 (11320 cm 2 g À1 ) accordingly. By referring the measured optical density of perfluorosulfonic acid (PFSA) at the F 1s peak at 690 eV (Martens et al, 2019), we could estimate the photoabsorption cross section Exp: Nafion at 690 eV to be about 23540 cm 2 g À1 . By using these photoabsorption cross sections and the density of Nafion 117, we calculated the transmission T(E x ) for each excitation energy as shown in Table 1.…”
Section: X-ray Absorbed Dose For the Typical Xrf Experimentsmentioning
confidence: 99%
“…‡ Calculated based on the Beer-Lambert law. § Evaluated from the measured optical density (Martens et al, 2019). } A 50 nm layer thickness was assumed.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…We should note here that radiation damage is always a problem in SX spectromicroscopy, especially for biological and polymer samples. To advance the microspectroscopic study of polymer samples, Wang and Hitchcock et al quantitatively evaluated the radiation-induced damage of polymer samples by using scanning TXM and X-PEEM [35][36][37]. We also study the radiation-induced damage of resinous samples here at SPring-8 [38,39].…”
Section: Plos Onementioning
confidence: 99%
“…Photo-absorption leads to excitation of electrons and subsequent decay channels that are dominated by the release of lowenergy secondary electrons and, thus, the basic processes of radiation damage are very similar to those in electron beam methods [17,24,79]. Several studies have investigated radiation damage in Xray microscopy with respect to resonant and non-resonant excitation, radiation chemistry and fundamental decomposition principles-mainly for soft organic matter [79][80][81][82][83][84][85][86][87][88][89][90][91][92]. All investigations found that X-ray induced chemistry can be quantitatively correlated with the absorbed dose d that is calculated by [83,87]: An important limitation in X-ray microscopy is radiation damage.…”
Section: Introductionmentioning
confidence: 99%